ANALISIS GAYA KEPEMIMPINAN KOMBINASI TRANSAKSIONAL DAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN PADA MASA PANDEMI COVID 19 DI KLINIK INTAN MEDIKA PANGKALPINANG - Danny; Zamhari; Shinta Lestari, Deara (Jurnal Ilmiah Niaga Bisnis Elektronik, 2022)
This research was entitled: “Analisis Gaya Kepemimpinan Kombinasi; Transactional dan Transformational Terhadap Kinerja Karyawan Pada Masa Pandemi Covid 19 di Klinik Intan Medika Pangkalpinang”. The purpose of this study was to determine and analyze the influence of leadership on the work performance of employees at the Intan Medika Clinic. Examine and analyze the influence of transformational leadership style on the work performance of employees at the Intan Medika Clinic. To examine and analyze the influence of transactional leadership style on the work performance of employees at the Intan Medika Clinic. To examine and analyze the dominant influence of the leadership style consisting of transformational and transactional or a combination on the work performance of employees at the Intan Medika Clinic. Either partially or simultaneously with a total of 90 pages without attachments. For the results of the coefficient of determination Adjusted R2 of 0.490 or can be defined as equivalent to 49%. It can be concluded that the influence of employee performance can be explained by a combination of leadership styles; transactional, and transformational during the Covid 19 Pandemic Period at the Intan Medika Clinic Pangkalpinang by 49%. There is a positive and significant effect of the combined leadership style variable on employee performance during the Covid 19 Pandemic Period at the Intan Medika Clinic Pangkalpinang H0 was rejected, and H1 was accepted. This is proven by the value of 4,078 and the p-value < .001, then the decision H1 is accepted. There is a negative and significant effect of transactional leadership variables on employee performance during the Covid 19 Pandemic Period at the Intan Medika Clinic Pangkalpinang H0 is rejected, and H1 is accepted. This is proven by the value of (-3.168) and p-value of 0.004, then the decision H2 is accepted. There is a positive and insignificant effect of transformational leadership variables on employee performance during the Covid 19 Pandemic Period at the Intan Medika Clinic Pangkalpinang H0 is rejected, and H1 is accepted. This is proven by the value of 2,399 and p-value of 0.024, then the decision H3 is accepted. There is a positive and significant influence, namely; combined leadership style; transactional, and transformational on employee performance during the Covid 19 Pandemic Period at Intan Medika Clinic Pangkalpinang This is proven by the value of 9962 and p-value <.001, the decision is H4 accepted.